Half a chance - Lord, Cynthia (New York, NY : Scholastic Press, 2014)
Lucy, with her mother and her photographer father, has just moved to a small rural community in New Hampshire, and with her new friend Nate she plans to spend the summer taking photos for a contest, but pictures sometimes reveal more than people are willing to see.
Keywords: Photography -- Juvenile fiction; Fathers and daughters -- Juvenile fiction; Friendship -- Juvenile fiction; New Hampshire -- Juvenile fiction; Photography -- Fiction; Fathers and daughters -- Fiction; Friendship -- Fiction; New Hampshire -- Fiction; Fathers and daughters; Friendship; Photography; New Hampshire; Fiction; Juvenile works